137Cs and 210Pbex dating to assess sedimentation rates in terraced valley floor fields - Yunqi Zhang; Shucui Liu; Dan Li; Wei Li; Qingfang Tan; Yi Long; Guirong Hou; Ziteng Luo; Haiyan Yi; Yong Wang; Bo Tan (Journal of Hydrology, 2026)

β,β-Dimethylacrylshikonin Alleviates Zebrafish (Danio rerio) Soyasaponin-Induced Enteritis by Maintaining Intestinal Homeostasis and Improving Intestinal Immunity and Metabolism - Ming Liu; Xin Lu; Leong-Seng Lim; Yinhui Peng; Lulu Liu; Kianann Tan; Peng Xu; Mingzhong Liang; Yingrui Wu; Qingfang Gong; Xiaohui Cai (Fishes, 2025)
Soyasaponin intolerance is common in ancient fish species, making them susceptible to enteritis caused by dietary soybean meal. β,β-Dimethylacrylshikonin is the key active monomer found in Lithospermum erythrorhizon and is known for its multiple pharmacological activities. However, its effect on soybean meal-induced enteritis remains unknown. The administration of 2 g/kg of β,β-Dimethylacrylshikonin (LE) effectively alleviated 5 g/kg of soyasaponin-induced histopathological changes and dysfunction, as evidenced by the expression of inflammation-related genes (il-1β, il-8, and il10). Regarding the gut microbiota composition, LE therapy decreased the population of inflammation-linked Proteobacteria and concurrently elevated the proportion of Fusobacteriota, effectively sustaining the balance of the zebrafish gut microbiota. Moreover, at the genus level, LE treatment also increased the abundance of Cetobacterium. Transcriptional results suggested that LE intervention mainly regulated immune-related pathways, including cytokine–cytokine receptor interaction, the TGF-beta signaling pathway, taurine and hypotaurine metabolism, and arachidonic acid metabolism. In conclusion, 5 g/kg of soyasaponins caused intestinal injury in zebrafish, and β,β-Dimethylacrylshikonin can reduce intestinal inflammation by regulating the intestinal microbial balance and metabolic disorder, with the best effect at 2 g/kg.

Gelatin based preservation technologies on the quality of food: a comprehensive review - Qingfang Ying; Shengnan Zhan; Haixia Yu; Jihua Li; Ru Jia; Huamao Wei; Eugeni Roura; Xinle Tan; Zhaohui Qiao; Tao Huang (Critical Reviews in Food Science and Nutrition, 2025)

Effects of Sophora flavescens ethanol extract supplementation in high soybean meal diets on growth, intestinal antioxidant status and immune response in Pearl Gentian grouper (Epinephelus fuscoguttatus♀ × E. lanceolatus♂) - Xin Lu; Yinhui Peng; Kianann Tan; Bingxiang Zhou; Qingfang Gong; Peng Xu; Xueying Liang; Wenjie Liu; Kit Yue Kwan; Yingrui Wu; Xiaohui Cai (Aquaculture International, 2025)

Effects of Sophora flavescens dietary supplementation on the growth performance, haematological indices, and intestinal bacterial community of Oreochromis niloticus - Xin Lu; Yingrui Wu; Yinhui Peng; Wenjie Liu; Ming Liu; Peng Xu; Kianann Tan; Xueying Liang; Xiaohui Cai; Qingfang Gong (Journal of Fish Biology, 2024)
Sophora flavescens is considered to be of various medicinal and economic importance. Previous studies have shown that it has antibacterial, antioxidant, and immune‐enhancing functions. To explore the full potential of S. flavescens in fish feed development, we investigated the effects of different levels of S. flavescens added to the diet on the growth performance, haematological indices, and the intestinal bacterial community of Nile tilapia ( Oreochromis niloticus ). The feeding trial lasted for 56 days, and the initial weight of the fish was 40.00 ± 5.00 g. Nile tilapia were randomly divided into six groups: a control group (CN) and five S. flavescens supplementation groups (0.02%, 0.04%, 0.08%, 0.16%, and 0.3% [w/w] of S. flavescens in diet). The growth performance of fish increased first and then decreased with the increase of S. flavescens supplemental level. Compared with other experimental groups, the growth performance of fish supplemented with 0.08% S. flavescens was significantly improved ( p S. flavescens , reaching the highest level at 0.08% ( p S. flavescens and reached the lowest value at 0.08% ( p S. flavescens was 0.04% in each treatment group ( p Bacteroides dominated the gut communities, and compared with the control group, two uncultured bacteria were suppressed. In addition, when the supplemental level of S. flavescens was more significant than 0.04%, the proliferation of Arcobacter cryaerophilus , Solibacillus silvestris , and Escherichia sp. in the gut of Nile tilapia was promoted. The results revealed that S. flavescens , as an additive to the Nile tilapia diet with levels ranging from 0.04% to 0.08%, can enhance the growth performance and immunity and promote the proliferation of intestinal beneficial bacteria of Nile tilapia.

Extracting Named Entity Using Entity Labeling in Geological Text Using Deep Learning Approach - Qinjun Qiu; Miao Tian; Zhong Xie; Yongjian Tan; Kai Ma; Qingfang Wang; Shengyong Pan; Liufeng Tao (Journal of Earth Science, 2023)

Determination of zinc contents in rabbits with cerebral ischemia by NAA and ICP-AES - Yinsong Wang; Huifang Zhao; Tianxi Zhang; Mingguang Tan; Guisun Zhuang; Baolin Chen; Zongzhi Huang; Hengli Tian; Qingfang Sun (Biological Trace Element Research, 1999)